ABUL MUIN AN-NASAFI – THE PROMOTER OF TEACHING OF "MOTURIDIYA". (Journal of Universal Science Research, 2023)
In this article, the scientific and spiritual heritage of Abu-l Mu'in al-Nasafi and the promotion of Moturidiya doctrine through the study and analysis of the works of Nasafi as a reformer of Moturidiya doctrine are highlighted through the sources.